Aerospace series. Cable, electrical, fire resistant. Single and twisted multicore assembly, screened (braided) and jacketed. Operating temperatures between - 65 °C and 260 °C. Technical specification Part 001, (27th September 2019) - British Standards Institution,
No abstract available